APPLICATION OF TAGUCHI EXPERIMENTAL DESIGN IN THE MANUFACTURING OF CORN COMB BRICK - Nurmaiyati Zamzamiyah; Meriana Wahyu Nugroho (Universitas Islam Malang, 2022)
Utilization for corn cobs as a substitute for aggregate for making bricks, can be used as an environmentally friendly non-structural construction material. This study aims to obtain the optimal composition and quality of bricks. The data collection technique use 36 samples in the form of bricks measuring 30 x 15 x 10 cm, with details of 18 brick samples for compressive strengths testing and 18 samples for wear resistance testing, variations in the addition of corn cobs 5%, 10% and 20%. The data analysis technique used the Taguchi method, with three levels and four factors. The results of the research show that the factors that influence the quality characteristics of the compressive strength and wear resistance of the brick are cement (1.992 kg), corn cobs (0.027 kg) and sand (3.110 kg). With a formulation based on SNR Larger the better at the compressive strength of bricks, namely (A3) cement level 3 and (C1) corn cobs level 1. While the wear resistance results based on Smaller is better are (B3) sand at level 3.